If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -2x + 19x + 7 Reorder the terms: y = 7 + -2x + 19x Combine like terms: -2x + 19x = 17x y = 7 + 17x Solving y = 7 + 17x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 7 + 17x
| x/7+x/3=10/21 | | 16x=6x | | x/0.8=x+5 | | 2x+10=3(x-1) | | 10-2x=-8x+10 | | 5y+3y=27-y | | 2(x-4)=x-8 | | x^2-12x+8=5 | | 2x^3+7x^2-162x-567=0 | | 15-3x=3x | | 2(y+8)=3(y-2) | | A=b+8 | | 9x=22+7x | | -4x+24=-44 | | 4x-1=67+x | | 8-a-9=7a-6 | | -4x+24=-24 | | 7x-11=-67 | | 5-4x=-6x+5 | | 5z^3+15z^2= | | 6y^2-12y=gcf | | 2(x-5)-4=0 | | -6(x+1)-11=32+5 | | 9-2x=x-27 | | ln(x+11)-ln(x-3)=ln(3) | | 7(5c-1)-8=33c+7 | | 2x^4-4x^3-x^2+2x=gcf | | -24=21x | | -3x+5=-31-7x | | 3x+9=10y+8 | | 5z^3+15z^2+3z+9= | | 16x+4y=7 |